The Effect of Discipline and Motivation on Performance Through Competence - Purwanti, Purwanti; Suswati, Endang; Navi , Navi (International Journal Labs, 2024)
In the modern work environment, discipline and work motivation are important factors that affect employee performance. Competency skills also play a role as a mediator in improving these performance. This study aims to analyze the influence of work discipline and motivation on employee performance through work competence at the One-Stop Integrated Service Office (DPMPTSP) of Mojokerto Regency. This study uses an explanatory research approach with a population of 50 ASN employees in DPMPTSP. The sample technique used was saturated sampling, with the entire population as a sample. Data were collected through questionnaires and analyzed using pathway analysis after going through validity, reliability, and classical assumption tests (multicollinearity, heteroscedasticity, and normality). The results of the analysis show that: (1) Work discipline has a significant positive effect on competence, (2) Work motivation has a significant positive effect on competence, (3) Work discipline has a significant positive effect on employee performance, (4) Work motivation has a significant positive effect on employee performance, (5) Competence has a significant positive effect on employee performance, (6) Work discipline has a significant positive effect on employee performance through competence, and (7) Work motivation has a significant positive effect on employee performance through competence. This research has implications for the importance of discipline and work motivation in improving employee performance with the role of competency mediation. This result is expected to be a reference for human resource management in the work environment to improve performance through increasing employee discipline, motivation, and competence